2012
DOI: 10.1155/2012/854837
|View full text |Cite
|
Sign up to set email alerts
|

Human Sperm Cryopreservation: Update on Techniques, Effect on DNA Integrity, and Implications for ART

Abstract: Cryopreservation of human spermatozoa—introduced in the 1960's—has been recognized as an efficient procedure for management of male fertility before therapy for malignant diseases, vasectomy or surgical infertility treatments, to store donor and partner spermatozoa before assisted reproduction treatments and to ensure the recovery of a small number of spermatozoa in severe male factor infertility. Despite the usefulness of it, cryopreservation may lead to deleterious changes of sperm structure and function: wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(218 citation statements)
references
References 82 publications
5
187
0
9
Order By: Relevance
“…This can be done using fast freezing or slow freezing methods or with a programmable freezer. With all three methods, a low molecular weight cryoprotectant is added to a processed semen sample to prevent ice formation in sperm cells [Di Santo et al 2012]. These chemicals optimize osmotic pressure and pH, provide extracellular energy to sperm, and prevent bacterial contamination (they include antibiotics) [Anger et al 2003].…”
Section: Conventional Cryopreservation Techniques: Slow Rapid and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done using fast freezing or slow freezing methods or with a programmable freezer. With all three methods, a low molecular weight cryoprotectant is added to a processed semen sample to prevent ice formation in sperm cells [Di Santo et al 2012]. These chemicals optimize osmotic pressure and pH, provide extracellular energy to sperm, and prevent bacterial contamination (they include antibiotics) [Anger et al 2003].…”
Section: Conventional Cryopreservation Techniques: Slow Rapid and Pmentioning
confidence: 99%
“…This mixture protects sperm cell membranes and prevents osmotic stress within the cells [Anger et al, 2003]. However, glycerol can alter the acrosomal membrane and change the mitochondrial environment [Di Santo et al 2012].…”
Section: Conventional Cryopreservation Techniques: Slow Rapid and Pmentioning
confidence: 99%
“…It has also been shown that cryopreservation reduces the antioxidant activities of the spermatozoa, making them more sensitive to reactive oxygen injuries [16]. Elevated concentrations of reactive oxygen species and decreases of antioxidant enzymes cause cell death after cryopreservation [17,18]. It has been reported that normospermic samples have higher levels of polyunsaturated fatty acids than do oligospermic and asthenospermic samples and that the total antioxidant capacity was higher in normospermic samples than the oligospermic and oligoastenospermic groups before freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Routine use of sperm storage started in the 60's for patients who undergo gonadotoxic treatment [18]. More recently, sperm storage has also been proposed to patients presenting a very low sperm count or suspected at high risk of rapid decrease in the sperm count (possibly linked to several genetic origins of the oligozoospermia) and asking for Assisted Reproductive Techniques [19].…”
Section: Discussionmentioning
confidence: 99%